Pengaruh Literasi Keuangan, Financial Self Efficacy, dan Lifestyle terhadap Pengelolaan Keuangan Pribadi Mahasiswa/I Akuntansi - Riska Pradisa; Amelia Tirana Sita; Elfin Krisdayanti Hia; Fachruli Hayu Biyantarimelia; Dian Widiyati (AKUNTANSI 45, 2025)
This research aims to explore how lifestyle, financial literacy, and financial self-efficacy influence the financial management behavior of accounting students in 2025. A quantitative research design was applied using multiple linear regression analysis. Data were collected from 100 accounting students through questionnaires and analyzed using SPSS version 25. The analysis revealed that financial literacy (X1) and lifestyle (X3) significantly affect students’ financial management, while financial self-efficacy (X2) shows no significant impact. These results imply that students with better financial knowledge and a more disciplined lifestyle tend to manage their finances more effectively. Although financial self-efficacy does not show a strong effect, it still contributes positively to promoting responsible financial behavior. Overall, the interaction among these three variables plays a vital role in shaping students’ ability to manage personal finances wisely. Strengthening financial literacy and maintaining a well-balanced lifestyle are expected to enhance students’ financial awareness and help them achieve sustainable financial stability in the future.